(untitled) (Czech Journal of International Relations, 2022)
The author analyses in his contribution the attitudes of the scholars and ideologues of different Islamist movements in the Middle East towards the institution of the nation-state. He explains the Islamist conception of the Islamic Order, the Islamist model of the state. The model is based on the practical achievements of the Prophet Mohammad during the nascent years of the Islamic community (umma) in Medina and on the teachings of the government of the first four Arabic khalifas. This period is generally referred to as a ’Golden Age’.The article describes in detail the di!erent approaches of the Shi’ites and Sunnis to the state and to their ability to change or reform a political system. The author analyses the differences between the model of the Western secular democratic state and the contemporary ideas of Islamists about state functions. In this context the following are examined: the Islamist views on political pluralism, referendum, parliament democracy, the multi-party system, civil society, modernization, the separation of state from religion and the exercise of popular sovereignty generally. Special attention is devoted to aspects related to the implementation of the divine Islamic law (shari’a). The author considers the role of the shari’a in different historical periods. He compares the extreme views of Islamists on the character of internatonal relations with the contemporary non-confrontational approaches of Islamic reformists. Drawing on the programmes of Islamist groups he explains the basic economic and social principles of the Islamic state. The study concludes with a reflection on the causes of the current crisis of secular nation-states in the era of globalization and its impact on the regional situation and on the Euro-Mediterranean Partnerships.